2020
DOI: 10.3390/coatings10030196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Laser Wavelength on Harmful Effects on Granite Due to Biofilm Removal

Abstract: The colonization of stone-built monuments by different organisms (algae, fungi, lichens, bacteria, and cyanobacteria) can lead to biodeterioration of the stone, negatively affecting the artistic value of the heritage. To address this issue, laser cleaning has been widely investigated in recent years, due to the advantages it offers over traditional mechanical and chemical methods: it is gradual, selective, contactless, and environmentally friendly. That said, the laser parameters should be optimized in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…These results may; therefore, involve negative impacts regarding the possible effects of an increase in atmospheric CO 2 on the stone colonization and biodeterioration processes. An increase in growth of cyanobacterial biofilms and in pigment concentrations may exacerbate the aesthetic impact of these biofilms on stone-made cultural heritage and; therefore, lead to treatments being necessary (e.g., biocide coating [42], laser cleaning [43] or application of natural oils [44]) and/or loss of value. An essential strategy to prevent colonization and subsequent biodeterioration is the selection of appropriate materials for building, ornamental purposes or replacement.…”
Section: Discussionmentioning
confidence: 99%
“…These results may; therefore, involve negative impacts regarding the possible effects of an increase in atmospheric CO 2 on the stone colonization and biodeterioration processes. An increase in growth of cyanobacterial biofilms and in pigment concentrations may exacerbate the aesthetic impact of these biofilms on stone-made cultural heritage and; therefore, lead to treatments being necessary (e.g., biocide coating [42], laser cleaning [43] or application of natural oils [44]) and/or loss of value. An essential strategy to prevent colonization and subsequent biodeterioration is the selection of appropriate materials for building, ornamental purposes or replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, this technique has been amply studied on outdoor stone surfaces due to its advantages over traditional cleaning methods: it is controllable, selective, contactless, and environmentally friendly [ 67 , 68 ]. The main drawback is that every study case needs to be optimized.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Barreiro et al [ 68 ] investigated in vitro the effects of three different wavelengths (355, 532, and 1064 nm) of an Nd:YAG laser applied in removing a naturally developed sub-aerial biofilm from Vilachán granite, which is commonly used in monuments in the Northwest (NW) Iberian Peninsula. The results showed that a wavelength of 532 nm successfully removed the biofilm, but it induced the highest color modifications in the granite due to extraction of the kaolinite crackled layer and the Fe-rich segregations.…”
Section: Physical Methodsmentioning
confidence: 99%
“…This new technique seemed very promising for conservation treatments at a time where heritage objects needed cleaning more frequently [2]. Since Asmus' works, many studies on laser cleaning have been conducted and explored the differences induced by changing the laser parameters such as the emitting wavelength, the laser energy, and the pulse duration on different materials and various contaminants including biological colonization (lichens, algae) [3][4][5][6][7][8][9][10][11][12][13][14], black sulphated gypsum crusts [15][16][17][18][19][20][21][22][23][24], dirt and environmental soiling [25], corrosion products [26][27][28][29][30][31][32][33][34], or graffiti [35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: The Development Of Laser Cleaning For Heritage Conservationmentioning
confidence: 99%